Knowledge, attitudes and practices of general medical practitioners in developed countries regarding oral cancer: an integrative review. (7th April 2020) - Saraswat, Nidhi; Everett, Bronwyn; Pillay, Rona; Prabhu, Neeta; George, Ajesh
Abstract: Background: Oral cancer is a public health concern and is widespread in developing countries, particularly in South Asia. However, oral cancer cases are also rising in developed nations due to various factors, including smoking, viruses and increased migration from South Asia. In this context, the role of general medical practitioners (GPs) in identifying oral cancer is becoming increasingly important and, while some studies have explored their perspective about oral cancer, a synthesis of these results has not been undertaken. Objective: The objective of this integrative review is to synthesize existing evidence regarding oral cancer-related knowledge, attitudes and practices of GPs in developed countries. Methods: Four electronic databases were searched to identify studies focussing on the objective of this review. The inclusion criteria were: peer-reviewed English language publications; studies conducted in developed countries involving GPs; explored at least one study outcome (knowledge/attitudes/practices). No restrictions were placed on the publication date. Results: A total of 21 studies involving 3409 GPs were reviewed. Most studies revealed limited knowledge of GPs about emerging risk factors, such as betel nut chewing (0.8–50%). Significant variation (7–70%) was evident in routine oral examination practices of GPs. Most GPs felt unsure about diagnosing oral cancer and many (38–94%) raised the need for further education. No study explored the specific relevance of GPs' practices concerning South Asian immigrants. Conclusion: This review suggests the need for educational programs to enhance GPs' knowledge regarding oral cancer. Further research exploring oral cancer-related practices of GPs caring for South Asian immigrants is warranted.